1994
DOI: 10.1002/etc.5620130905
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of organotin compounds in the red sea bream (pagrus major) by two uptake pathways: Dietary uptake and direct uptake from water

Abstract: The bioaccumulation and elimination of organotin compounds in Pagrus major during dietary uptake and/or direct uptake from water were studied. When tributyltin (TBT) and triphenyltin (TPT) compounds were accumulated in fish from seawater and from feed simultaneously, about one‐quarter of the bioaccumulation was due to the dietary uptake. The biomagnification factors (BMFs) were 0.26 to 0.38 for TBT and 0.57 for TPT. BMF was not significantly altered by the concentration nor the species of chemicals in the feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Parameter uncertainty for the biomass cycle was described for the CATS-2 model (11). Recently, an assimilation efficiency of 9.5-12.7% was determined for the red sea bream (43). Basic statistics are log transformed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter uncertainty for the biomass cycle was described for the CATS-2 model (11). Recently, an assimilation efficiency of 9.5-12.7% was determined for the red sea bream (43). Basic statistics are log transformed.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that food uptake can be a significant portion of total TBT uptake for fish (43). It seems that the more a species feeds on benthic invertebrates, the higher the FWU ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments with early life stages of minnows (Phoxinus phoxinus, Fent, 1991) and Red Sea bream (Pagrus major, Yamada et al, 1993) indicate that triphenyltin has a high potential for bioaccumulation, since direct uptake from water across the gills as well as dietary uptake is rapid (Yamada et al, 1993), and both elimination and metabolization are extremely slow. Highest triphenyltin concentrations were measured in the liver (Yamada et al, 1993); in rainbow trout (Oncorhynchus mykiss) liver exposed to sublethal concentrations of TPTA for 4 weeks, for example, bioconcentration was by a factor of 2100}2700 (Schwaiger et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Highest triphenyltin concentrations were measured in the liver (Yamada et al, 1993); in rainbow trout (Oncorhynchus mykiss) liver exposed to sublethal concentrations of TPTA for 4 weeks, for example, bioconcentration was by a factor of 2100}2700 (Schwaiger et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, toxicologists are interested in studying the effects of chemicals, delivered via dietary exposure, on organisms. Previously, researchers have loaded chemicals into food using a 1:1 or higher ratios of solvent volume to food weight [1–3] or they have mixed [4] or ground the chemical of interest and food with a mortar and pestle [5]. Neither method seemed appropriate for the production of larger amounts (hundreds of grams per loading) of test diets involving hazardous chemicals.…”
Section: Introductionmentioning
confidence: 99%